A Meta-Analysis to Determine Strength Training Related Dose-Response Relationships for Lower-Limb Muscle Power Development in Young Athletes - Slimani, Maamer; Paravlic, Armin; Granacher, Urs (Frontiers in Physiology, 2018)
It is well-documented that strength training (ST) improves measures of muscle strength in young athletes. Less is known on transfer effects of ST on proxies of muscle power and the underlying dose-response relationships. The objectives of this meta-analysis were to quantify the effects of ST on lower limb muscle power in young athletes and to provide dose-response relationships for ST modalities such as frequency, intensity, and volume. A systematic literature search of electronic databases identified 895 records. Studies were eligible for inclusion if (i) healthy trained children (girls aged 6–11 y, boys aged 6–13 y) or adolescents (girls aged 12–18 y, boys aged 14–18 y) were examined, (ii) ST was compared with an active control, and (iii) at least one proxy of muscle power [squat jump (SJ) and countermovement jump height (CMJ)] was reported. Weighted mean standardized mean differences (SMDwm) between subjects were calculated. Based on the findings from 15 statistically aggregated studies, ST produced significant but small effects on CMJ height (SMDwm = 0.65; 95% CI 0.34–0.96) and moderate effects on SJ height (SMDwm = 0.80; 95% CI 0.23–1.37). The sub-analyses revealed that the moderating variable expertise level (CMJ height: p = 0.06; SJ height: N/A) did not significantly influence ST-related effects on proxies of muscle power. “Age” and “sex” moderated ST effects on SJ (p = 0.005) and CMJ height (p = 0.03), respectively. With regard to the dose-response relationships, findings from the meta-regression showed that none of the included training modalities predicted ST effects on CMJ height. For SJ height, the meta-regression indicated that the training modality “training duration” significantly predicted the observed gains (p = 0.02), with longer training durations (>8 weeks) showing larger improvements. This meta-analysis clearly proved the general effectiveness of ST on lower-limb muscle power in young athletes, irrespective of the moderating variables. Dose-response analyses revealed that longer training durations (>8 weeks) are more effective to improve SJ height. No such training modalities were found for CMJ height. Thus, there appear to be other training modalities besides the ones that were included in our analyses that may have an effect on SJ and particularly CMJ height. ST monitoring through rating of perceived exertion, movement velocity or force-velocity profile could be promising monitoring tools for lower-limb muscle power development in young athletes.